Seventh tumor-node-metastasis staging of gastric cancer: Five-year follow-up - Rausei, Stefano; Ruspi, Laura; Galli, Federica; Pappalardo, Vincenzo; Di Rocco, Giuseppe; Martignoni, Francesco; Frattini, Francesco; Rovera, Francesca; Boni, Luigi; Dionigi, Gianlorenzo (World journal of gastroenterology : WJG, 2016)
Seventh tumor-node-metastasis (TNM) classification for gastric cancer, published in 2010, introduced changes in all of its three parameters with the aim to increase its accuracy in prognostication. The aim of this review is to analyze the efficacy of these changes and their implication in clinical practice. We reviewed relevant Literature concerning staging systems in gastric cancer from 2010 up to March 2016. Adenocarcinoma of the esophago-gastric junction still remains a debated entity, due to its peculiar anatomical and histological situation: further improvement in its staging are required. Concerning distant metastases, positive peritoneal cytology has been adopted as a criterion to define metastatic disease: however, its search in clinical practice is still far from being routinely performed, as staging laparoscopy has not yet reached wide diffusion. Regarding definition of T and N: in the era of multimodal treatment these parameters should more influence both staging and surgery. The changes about T-staging suggested some modifications in clinical practice. Differently, many controversies on lymph node staging are still ongoing, with the proposal of alternative classification systems in order to minimize the extent of lymphadenectomy. The next TNM classification should take into account all of these aspects to improve its accuracy and the comparability of prognosis in patients from both Eastern and Western world.